Cavitation on a scaled-down model of a Francis turbine guide vane: high-speed imaging and PIV measurements; Journal of Physics: Conference Series; Vol. 656, conference 1 : 9th International Symposium on Cavitation (CAV2015) - Pervunin K. S.; Timoshevsky M. V.; Churkin S. A.; Kravtsova A. Yu.; Markovich D. M. Dmitry Markovich; Khanjyalich K. (2015, 2015)
Title screen